Causal association between epigenetic age acceleration and two pulmonary vascular diseases: pulmonary arterial hypertension and pulmonary embolism—a bidirectional Mendelian study - Jun Tong; Chuanxue Wan; An Wang; Mengqi Chen; Binqian Ruan; Jieyan Shen (Clinical Epigenetics)
Abstract Background Pulmonary arterial hypertension (PAH) is a relatively rare but severe disease with a poor prognosis. Pulmonary embolism (PE) is a serious condition that can cause sudden death. Epigenetic age acceleration (EAA) is a robust indicator derived from the DNA methylation-based epigenetic clock, which can predict the extent of aging. It has been proved that the epigenetic clock and EAA are associated with many cardiovascular diseases, while their associations with PAH and PE remain inconclusive. Our study aims to investigate the associations among these factors. Method By harnessing summary-level data from large-scale genome-wide association studies (GWAS), we designed a two-sample bidirectional Mendelian randomization (MR) analysis to assess the causal associations between measures of three epigenetic clocks, including GrimAge acceleration (n = 34,467), Hannum Age acceleration (n = 34,449) and PhenoAge acceleration (n = 34,463) and PAH (including 125 cases and 162,837 controls), as well as PE (including 3940 cases and 480,658 controls). The inverse variance-weighted (IVW) method was used as the primary method for MR analysis. Other methods, such as MR egger and weighted mode, served as complements to the IVW approach, were also applied in the analyses. Then, the MR pleiotropy test and MR-PRESSO test, which are effective tools for quality control of MR analysis, were subsequently used to ensure the accuracy of the study. Results The forward MR analysis indicated that all three epigenetic clocks had no significant effects on PAH or PE. The reverse analysis indicated that the onset and progression of PAH and PE had insignificant effects on three epigenetic clocks. The results of the quality control assessment confirmed that our findings were reliable. Conclusion Our two-sample bidirectional MR analysis suggested that there is no significant association between epigenetic clocks and these two pulmonary vascular diseases.